Effect of different levels of boron and its methods of application on growth and yield of cauliflower (Brassica oleracea var. botrytis L.) - Singh, KP; Singh, VK; Kamalkant; Roy, RK (Vegetable Science, 2011)
Cauliflower (Brassica oleracea var.botrytis L.) is an important vegetable crop of the plateau region of Chhotanagpur. Due to mild favourable temperature, cauliflower is grown almost throughout the year. The crop is highly remunerative and farmers get high return. The crop suffers from Boron deficiency (dead heart rot and hollow stem) in acidic soils of the region specially during the rainy season. Application of Boron significantly overcomes these problems and results in increased curd yield (Kotur and Kumar, 1980).